Navigating the Chiral Pool in the Total Synthesis of Complex Terpene Natural Products - Brill, Zachary G. (Chem Rev, 2017)
The pool of abundant chiral terpene building blocks (i.e. “chiral pool terpenes”) has long served as a starting point for the chemical synthesis of complex natural products, including many terpenes themselves. As inexpensive and versatile starting materials, such compounds continue to influence modern synthetic chemistry. This review highlights 21(st) century terpene total syntheses which themselves use small, terpene-derived materials as building blocks. An outlook to the future of research in this area is highlighted as well.